Tedhak siten: Antara tradisionalitas dan modernitas (potret eksistensi di jambi) - khasanah, uswatun - (Maliki Interdisciplinary Journal, 2025)
This article examines the tradition of tedhak siten, a Javanese ritual that marks the transition of a baby to toddlerhood by setting foot on the ground for the first time. The research focuses on the continuation of this tradition in Jambi Province, where Javanese culture also developed through migration. The tedhak siten tradition has deep meaning, including as a form of gratitude and prayer for the welfare of the child. However, its existence has been eroded by modernization and changes in social values, leading some communities to prefer simple thanksgiving over a full ceremony. This article reviews the factors influencing the decline of the tedhak siten tradition and suggests preservation efforts to maintain the inherited cultural values.